Storage losses, liquidity constraints, and maize storage decisions in Benin - Kadjo, D.; Ricker-Gilbert, J.; Abdoulaye, Tahirou; Shively, G.E.; Baco, M.N. (Wiley, 2018)
This article estimates how storage losses from mold, insects, and other pests, combined with liquidity constraints, influence a smallholder farm household's decision to store maize on farm after harvest. We analyze panel data from 309 smallholders in Benin covering the 2011 and 2013 harvest seasons. Results suggest that smallholders are driven to sell at harvest time for different reasons, depending on their motivation for storing. In households that report direct consumption as their primary goal for storing maize, liquidity constraints, not storage losses, reduce the amount they store. In contrast, households that store maize with the intention of selling it later in the year appear unaffected by liquidity constraints. Instead, these households store less when they expect to lose more during storage. These results suggest that policies to provide liquidity will be more helpful in motivating storage among consumption‐oriented households. Households motivated to store for later sale will benefit from modern storage technologies that mitigate the operational costs associated with storage losses.